Reduction of Resting Energy Expenditure and Sarcopenic Obesity in Adults with Overweight and Obesity: A Brief Report - Tannir, Hana; Kreidieh, Dima; Itani, Leila; El Masri, Dana; El Ghoch, Marwan (Current Diabetes Reviews, 2020)
Background and Aim: The last decade has seen the emergence of a new condition, describing the coexistence of obesity and sarcopenia, termed Sarcopenic Obesity (SO). The aim of this study was to assess the potential association between SO and reduced Resting Energy Expenditure (REE). Methods: Body composition and REE were measured using a bioimpedance analyser (Tanita BC-418) and Indirect Calorimeter (Vmax Encore 229), respectively in 89 adults with overweight or obesity of both genders, referred to the Outpatient Clinic of the Department of Nutrition and Dietetics at Beirut Arab University (Lebanon). Participants were then categorized on the basis of having SO or not. Results: Thirty-nine of the 89 participants met the criteria for SO (43.8%), and these participants displayed a significantly lower REE per unit body weight than those in the group without SO (19.02 ± 2.26 vs. 20.87 ± 2.77; p = 0.001). Linear regression analysis showed that the presence of SO decreases REE by 1.557 kcal/day for each kg of body weight (β = -1.557; CI = -0.261 – (-0.503); p = 0.004), after adjusting for age and gender. Conclusion: SO appears to be present in a high proportion of treatment-seeking adults with overweight or obesity of both genders, and it seems to be associated with a reduced REE, compared with those without SO. Future studies are needed to clarify whether this may influence clinical outcomes.
Keywords: reduced lean body mass